LEAN APPROACH: EVALUATION OF THE USE OF A MODULAR SHELF SYSTEM IN A PHARMACY SETTING IGD: LEAN APPROACH: EVALUATION OF THE USE OF A MODULAR SHELF SYSTEM IN A PHARMACY SETTING IGD - Yekti, Alfa Nugroho (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2024)
The lean hospital approach can be used as a reference for improving the hospital pharmacy installation service process. The research aims to use the lean hospital approach as a reference for improving the service process which focuses on outpatient pharmacy satellites and inpatient pharmacy satellites at X Private Hospital Yogyakarta. This research uses a non-experimental research design with a qualitative approach. Value data was obtained using questionnaire measuring instruments, direct observation, in-depth interviews, unstructured interviews and review of related documents. The effort taken by researchers to maintain data validity is data triangulation. The data obtained was analyzed using descriptive analysis. The results show that reducing activities that do not provide added value for customers results in a decrease in the value of waste (Non Value-added Activity) by 49.87%, Optimizing inventory control reduces 23.83% (Rp. 55,210,830.45) and increases the efficiency of taking pharmaceutical supplies is 4.8 hours